WorldView 1 - Rost, Michael (Longman, 2005)
WorldView, a four-skills course for adult learners of English, builds fluency by exposing students to a wide range of appealing topics. The course's two-page lessons-2 per unit-present clear and attainable goals, ensuring that students feel a sense of accomplishment and increased self-confidence